The Global Availability of Rabies Immune Globulin and Rabies Vaccine in Clinics Providing Indirect Care to Travelers. Issue 1 (25th November 2013) - Jentes, Emily S.; Blanton, Jesse D.; Johnson, Katherine J.; Petersen, Brett W.; Lamias, Mark J.; Robertson, Kis; Franka, Richard; Muhm, Daniel; Rupprecht, Charles E.; Marano, Nina; Brunette, Gary W.
Abstract We assessed rabies vaccine (RV) and immune globulin (RIG) availability on the local market by querying US Embassy medical staff worldwide. Of 112 responses, 23% were from West, Central, and East Africa. RV and RIG availability varied by region. Possible rabies exposures accounted for 2% of all travelers' health inquiries.